2020
DOI: 10.1175/jcli-d-19-0624.1
|View full text |Cite
|
Sign up to set email alerts
|

The Opposing Effects of Reforestation and Afforestation on the Diurnal Temperature Cycle at the Surface and in the Lowest Atmospheric Model Level in the European Summer

Abstract: The biophysical effects of re/af-forestation on the diurnal temperature cycle in European summer are investigated by analyzing a Regional Climate Model (RCM) ensemble, established within the Land Use and Climate Across Scales Flagship Pilot Study (LUCAS FPS). With this RCM ensemble, two idealized experiments are performed for Europe, one with a continent with maximized forest cover, and one where all forests are turned into grassland. First, an in-depth analysis of one ensemble member (CCLM-VEG3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
6
34
0
1
Order By: Relevance
“…Bonan, 2008), since at least in Southern and Central Europe evapotranspiration is reduced in FOREST (Figure 2a). As stated by Breil et al, (2020), the lower surface temperatures in FOREST are mainly caused by increased sensible heat fluxes all over Europe (Figure 5c), which transform and transport the increased energy input from the net short-wave radiation into the atmosphere, without increasing the surface temperature.…”
Section: Effects Of Surface Roughnessmentioning
confidence: 85%
See 1 more Smart Citation
“…Bonan, 2008), since at least in Southern and Central Europe evapotranspiration is reduced in FOREST (Figure 2a). As stated by Breil et al, (2020), the lower surface temperatures in FOREST are mainly caused by increased sensible heat fluxes all over Europe (Figure 5c), which transform and transport the increased energy input from the net short-wave radiation into the atmosphere, without increasing the surface temperature.…”
Section: Effects Of Surface Roughnessmentioning
confidence: 85%
“…CC BY 4.0 License. Due to a higher surface roughness, the daily maximum surface temperatures (top of the vegetation) of a forest are lower than 275 of grassland (Breil et al, 2020). The saturation deficit between the vegetation and the atmosphere (1), which depends on these surface temperatures (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) and Breil et al. (2020). This is important for snow related variables (e.g., snow depth, cover/extent and snow water equivalent) that are critical for representing accumulation and ablation processes at the surface.…”
Section: Discussionmentioning
confidence: 96%
“…The comparison is further complicated by the use of 2 m air temperature in studies by Davin et al (2020). Recent studies such as the multimodel study of Breil et al (2020) have demonstrated the fallibility of using 2 m air temperature, a diagnostic variable, to assess LULCC. In particular, they show that different models can provide conflicting results in summer when using 2 m air temperature but that differences can be reconciled when surface temperature is used instead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation